2013
DOI: 10.1200/jco.2012.42.9829
|View full text |Cite
|
Sign up to set email alerts
|

New Targetable Oncogenes in Non–Small-Cell Lung Cancer

Abstract: A B S T R A C TThe identification of oncogenic driver mutations underlying sensitivity to epidermal growth factor receptor and anaplastic lymphoma kinase tyrosine kinase inhibitors has led to a surge of interest in identifying additional targetable oncogenes in non-small-cell lung cancer. A number of new potentially oncogenic gene alterations have been characterized in recent years, including BRAF mutations, HER2 insertions, PIK3CA mutations, FGFR1 amplifications, DDR2 mutations, ROS1 rearrangements, and RET r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
207
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(211 citation statements)
references
References 76 publications
1
207
0
3
Order By: Relevance
“…The EML4-ALK fusion gene is found in 3%-5% of NSCLCs, and is detected by the U.S. Food and Drug Administration (FDA)-approved companion diagnostic breakapart fluorescence in situ hybridization (FISH) assay from Vysis (Abbott Laboratories, Abbott Park, IL, https://www. abbottmolecular.com), as well as a more recently approved immunohistochemistry (IHC) assay [2,3]. EML4-ALK fusions in NSCLC occur in at least 8 variants, with all known variants having a breakpoint in intron 19 of ALK, but with a variety of introns in EML4 experiencing rearrangement, resulting in inclusion of differing fragments of the N-terminal region of EML4 [4].…”
Section: Introductionmentioning
confidence: 99%
“…The EML4-ALK fusion gene is found in 3%-5% of NSCLCs, and is detected by the U.S. Food and Drug Administration (FDA)-approved companion diagnostic breakapart fluorescence in situ hybridization (FISH) assay from Vysis (Abbott Laboratories, Abbott Park, IL, https://www. abbottmolecular.com), as well as a more recently approved immunohistochemistry (IHC) assay [2,3]. EML4-ALK fusions in NSCLC occur in at least 8 variants, with all known variants having a breakpoint in intron 19 of ALK, but with a variety of introns in EML4 experiencing rearrangement, resulting in inclusion of differing fragments of the N-terminal region of EML4 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is one of the most common cancer types all over the world, and a number of previous studies have identified a large quantity of lung cancer driver genes, such as EGFR, Her2, AKT1, NRAS, PIK3CA, BRAF, ALK-fusion and RET-fusion (5)(6)(7)(8). Somatic mutations of these genes have been recurrently identified in lung cancer samples (5)(6)(7)(8). However, unlike in sporadic lung cancer, the molecular mechanisms behind inherited lung cancer remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, epidermal growth factor receptor (EGFR) mutations (6), EML4/ALK fusion genes (7), RAS mutations, BRAF mutations and PI3K/mTOR mutations are frequently observed in lung cancer tissues, and are predictive of response to targeted therapies (8).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that amplification or overexpression of this gene has been shown to play an important role in the pathogenesis and progression of certain types of cancer (17,25,26). In breast cancer, ErbB2 was found to upregulate b-catenin via inactivation of GSK-3b by the Erk pathway (13).…”
Section: Discussionmentioning
confidence: 99%